Lactobacillus paracasei 28.4 reduces in vitro hyphae formation of Candida albicans and prevents the filamentation in an experimental model of Caenorhabditis elegans - de Barros, Patrícia Pimentel [UNESP]; Scorzoni, Liliana [UNESP]; Ribeiro, Felipe de Camargo [UNESP]; Fugisaki, Luciana Ruano de Oliveira [UNESP]; Fuchs, Beth Burgwyn; Mylonakis, Eleftherios; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP]; Rossoni, Rodnei Dennis [UNESP] (Elsevier, 2018)
The objective of this study was to evaluate the influence of microbe-microbe interactions to identify a strain of Lactobacillus that could reduce the filamentation of Candida albicans ATCC 18804 using in vitro and in vivo models. Thus presenting a probiotic effect against the fungal pathogen. First, we analyzed the ability of 25 clinical isolates of Lactobacillus to reduce filamentation in C. albicans in vitro. We found that L. paracasei isolate 28.4 exhibited the greatest reduction of C. albicans hyphae (p = 0.0109). This reduction was confirmed by scanning electron microscopy analysis. The influence of C. albicans filamentation was found to be contributed through reduced gene expression of filament associated genes (TEC1 and UME6). In an in vivo study, prophylactic provisions with L. paracasei increased the survival of Caenorhabditis elegans worms infected with C. albicans (p = 0.0001) by 29%. Prolonged survival was accompanied by the prevention of cuticle rupture of 27% of the worms by filamentation of C. albicans, a phenotype that is characteristic of C. albicans killing of nematodes, compared to the control group. Lactobacillus paracasei isolate 28.4 reduced the filamentation of C. albicans in vitro by negatively regulating the TEC1 and UME6 genes that are essential for the production of hyphae. Prophylactic provision of Lactobacillus paracasei 28.4 protected C. elegans against candidiasis in vivo. L. paracasei 28.4 has the potential to be employed as an alternative method to control candidiasis.
Keywords: Candida albicans; Gene expression; Lactobacillus; Pathogenesis; Probiotics; Yeasts